Multiple giant diverticula of the jejunum causing intestinal obstruction: report of a case and review of the literature - Archontovasilis Fotis; Mathioulakis Stavros; Vlachos Konstantinos; Falidas Evangelos; Villias Constantinos (World Journal of Emergency Surgery, 2011)
Abstract Multiple diverticulosis of jejunum represents an uncommon pathology of the small bowel. The disease is usually asymptomatic and must be taken into consideration in cases of unexplained malabsorption, anemia, chronic abdominal pain or discomfort. Related complications such as diverticulitis, perforation, bleeding or intestinal obstruction appear in 10-30% of the patients increasing morbidity and mortality rates. We herein report a case of a 55 year-old man presented at the emergency department with acute abdominal pain, vomiting and fever. Preoperative radiological examination followed by laparotomy revealed multiple giant jejunal diverticula causing intestinal obstruction. We also review the literature for this uncommon disease.